Effect of tempe gembus on cholesterol profile in hyperlipidemic rats (Faculty of Medicine Universitas Indonesia, 2007)
Atherosclerosis and coronary heart disease has become a prominent health problem in Indonesia. High blood lipid level is considered to be among the risk factors, that can be controlled by dietary treatment. Like tempe kedele, tempe gembus, a nutritious food, is known to contain many substances that is able to influence blood lipid level. This study was conducted to investigate the effect of various concentrations of tempe gembus on blood lipid profile in hyperlipidemic rats. Tempe gembus were given in variations of 0%, 4%, 8%, and 12% (w/w). The result of this study showed that 0% tempe gembus decreased triglyceride, total cholesterol, and HDL cholesterol level, and cholesterol HDL/LDL ratio, and increased LDL cholesterol level. Four percent tempe gembus increased triglyceride level, decreased total cholesterol, LDL and HDL cholesterol level, and increased HDL/LDL ratio; 8% tempe gembus increased triglyceride level, decreased total cholesterol, LDL, and HDL cholesterol level, and increased HDL/LDL ratio; 12% tempe gembus increased triglyceride level, decreased total cholesterol, LDL, and HDL cholesterol level, and increased HDL/LDL ratio. However, a significant effect of tempe gembus were only the decrease in total cholesterol, and LDL cholesterol (8% and 12% treatment), and increase in cholesterol HDL/ LDL ratio only happend in 8 % treatment. (Med J Indones 2007; 16:205-11)